"Iatrogenic" Segmental Defect: How I Debride High-Energy Open Tibial Fractures. Issue 5 (October 2017) - Southam, Brendan R.; Archdeacon, Michael T.
Abstract : Summary: High-energy, open tibial shaft fractures may result in significant comminution, bone loss, and soft tissue injuries. Early, thorough debridement of all nonviable tissue is of critical importance in treating these fractures as an inadequate initial debridement increases the risk of infection and nonunion. Large iatrogenic bone and soft tissue defects can result from debridement and will require subsequent reconstruction by both orthopaedic and plastic surgeons. Although a variety of approaches exist to address these reconstructions, successful management of bone defects remains a considerable challenge. In this article, we detail our approach to debridement and reconstruction of segmental tibial defects and provide a review on the literature on this topic. Abstract : Supplemental Digital Content is Available in the Text.